1978
DOI: 10.1136/gut.19.6.563
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular electrolyte depletion in patients with ileostomies.

Abstract: SUMMARY Fourteen apparently healthy patients with ileostomies were found to be depleted of total exchangeable sodium and potassium, but had normal serum electrolyte concentrations and normal extracellular fluid and total body water volumes. The low exchangeable sodium and potassiums were thus primarily due to depletion of the intracellular compartment. There was no evidence of renal or intestinal conservation of these ions and plasma aldosterone, renin activity, and prolactin concentrations were normal in most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Even if the results of the single patient with Crohn's disease are excluded from our study, the findings remain unchanged. It is of interest that the present study has shown a significant reduction in total body potassium in ileostomy patients similar to that reported by Turnberg et al 9 As the reduction is of the same magnitude for both our groups of ileostomists, this suggests that it is attributable to proctocolectomy alone rather than to ileal resection. Furthermore, accompanying the fall in total body potassium there were comparable reductions in total body nitrogen in both groups of patients, and together these findings indicate a reduction of fat free mass.…”
Section: Discussionsupporting
confidence: 91%
“…Even if the results of the single patient with Crohn's disease are excluded from our study, the findings remain unchanged. It is of interest that the present study has shown a significant reduction in total body potassium in ileostomy patients similar to that reported by Turnberg et al 9 As the reduction is of the same magnitude for both our groups of ileostomists, this suggests that it is attributable to proctocolectomy alone rather than to ileal resection. Furthermore, accompanying the fall in total body potassium there were comparable reductions in total body nitrogen in both groups of patients, and together these findings indicate a reduction of fat free mass.…”
Section: Discussionsupporting
confidence: 91%
“…9 In healthy volunteers, experimentally induced sodium depletion was followed by a decreased ability to taste, anorexia, nausea, cramps, exhaustion, and impaired mental functions, as well as weight loss and a negative nitrogen balance. 10 Although patients with an ileostomy may appear healthy and have normal plasma sodium values, 1,3,11,12 careful interviewing may reveal such symptoms, and symptoms resolve following sodium repletion. 13 Sodium and fluid balances are mainly regulated renally through neurohumoral and pressure-mediated mechanisms as a response to the total body sodium and the effective extracellular volume.…”
Section: Introductionmentioning
confidence: 99%
“…Increased effluents generally result in a loss of water and salt in patients undergoing total colectomy, conditions which stimulates the renin-angiotensinaldosterone system and consequently increases the level of aldosterone production (Gallagher et al 1962). In our clinical study at Tohoku University Hospital, the majority of colectomized patients demonstrated high plasma aldosterone concentration as compared with normal subjects (unpublished observations), although there are some conflicting reports claiming that aldosterone concentrations are within normal limits in ileostomates (Issacs et al 1976;Turnberg et al 1978). Our present study indicates that circulating aldosterone acts not only on the kidney but also on remnant ileum, and increased and/or de novo expression of mineralocorticoid receptor and increased aldosterone output may play an important role in intestinal adaptation in these patients.…”
Section: Discussionmentioning
confidence: 99%